2003
DOI: 10.1090/s0002-9939-03-07311-8
|View full text |Cite
|
Sign up to set email alerts
|

Primes generated by elliptic curves

Abstract: Abstract. For a rational elliptic curve in Weierstrass form, Chudnovsky and Chudnovsky considered the likelihood that the denominators of the xcoordinates of the multiples of a rational point are squares of primes. Assuming the point is the image of a rational point under an isogeny, we use Siegel's Theorem to prove that only finitely many primes will arise. The same question is considered for elliptic curves in homogeneous form, prompting a visit to Ramanujan's famous taxi-cab equation. Finiteness is provable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…However, a heuristic argument (discussed later) using the prime number theorem was adapted in [7], and it suggested that a nonlinear Somos sequence should contain only finitely many prime terms. See [9] for proofs in some special cases.…”
Section: Is Through the (Binary) Linear Recurrence Relationmentioning
confidence: 99%
“…However, a heuristic argument (discussed later) using the prime number theorem was adapted in [7], and it suggested that a nonlinear Somos sequence should contain only finitely many prime terms. See [9] for proofs in some special cases.…”
Section: Is Through the (Binary) Linear Recurrence Relationmentioning
confidence: 99%
“…Somos 4 sequences, and EDS in particular, are of considerable interest to number theorists due to the way that primitive prime divisors appear [6,7,9,10,11,12,35]. In that and in other respects, they have a lot in common with linear recurrence sequences (see [8, chapters 10 and 11]).…”
Section: Introductionmentioning
confidence: 99%
“…Building on the heuristic argument above, Einsiedler et al [10] conjectured that an EDS has only finitely many prime terms, and this conjecture was later expanded upon by Everest et al [13]. For some EDSs, finiteness follows from a type of generic factorization not unlike (2.1) (see, for example, [13,14,16,26] and Section 6), but the general case appears difficult. The study of primitive divisors in integral Lucas sequences goes back to the 19th-century work of Bang [2] and Zsigmondy [57], who showed that a n − b n has a primitive divisor for all n > 6.…”
Section: History and Motivationmentioning
confidence: 99%